The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1158/1078-0432.ccr-16-0558
|View full text |Cite
|
Sign up to set email alerts
|

HER3 Targeting Sensitizes HNSCC to Cetuximab by Reducing HER3 Activity and HER2/HER3 Dimerization: Evidence from Cell Line and Patient-Derived Xenograft Models

Abstract: Purpose Our previous work suggested that HER3 inhibition sensitizes HNSCC to EGFR inhibition with cetuximab. This study aimed to define the role of HER3 in cetuximab resistance and the anti-tumor mechanisms of EGFR/HER3 dual targeting in HNSCC. Experimental Design We treated cetuximab-resistant HNSCC UMSCC1-C and parental UMSCC1-P cell lines with anti-EGFR antibody cetuximab, anti-HER3 antibody MM-121, and their combination. We assessed activities of HER2, HER3 and downstream signaling pathways by Western bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 50 publications
4
60
0
1
Order By: Relevance
“…[24][25][26][27][28][29] However, in cetuximab-treated SNU1076 cells, MET activation reduced the phosphorylation levels of both HER2 and HER3 (Fig. As expected, we observed an increase of phosphorylated HER2 and HER3, which are known to be elevated in response to cetuximab in different types of cancer, including in HNSCC.…”
Section: Met/mapk Pathway Activation Abolishes Cetuximab-induced Her2supporting
confidence: 77%
See 2 more Smart Citations
“…[24][25][26][27][28][29] However, in cetuximab-treated SNU1076 cells, MET activation reduced the phosphorylation levels of both HER2 and HER3 (Fig. As expected, we observed an increase of phosphorylated HER2 and HER3, which are known to be elevated in response to cetuximab in different types of cancer, including in HNSCC.…”
Section: Met/mapk Pathway Activation Abolishes Cetuximab-induced Her2supporting
confidence: 77%
“…[3][4][5][12][13][14] Cetuximab inhibits tumor cell growth by preventing ligand binding to the extracellular domain of EGFR, thereby preventing the dimerization and auto-phosphorylation of this receptor and the subsequent activation of the signaling pathways downstream of EGFR. [24][25][26] The activation of the HER2/HER3 feedback loop in response to anti-EGFR therapies has also been reported in other cancers such as lung, breast and colorectal cancers. [19][20][21][22] An additional common resistance mechanism to cetuximab is reactivation of signaling pathways due to upregulation and activation of alternative RTKs, which termed as a compensatory activation loop [reviewed in Ref.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…7 Publications have shown that the amplification or increased level of MET, ERBB2 or ERBB3 contributes to consecutive activation of the downstream signaling of EGFR, leading to tumor resistance to EGFR-targeted treatment, while targeting them resensitizes tumor to cetuximab. 7 Publications have shown that the amplification or increased level of MET, ERBB2 or ERBB3 contributes to consecutive activation of the downstream signaling of EGFR, leading to tumor resistance to EGFR-targeted treatment, while targeting them resensitizes tumor to cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Combined application of cetuximab and conventional chemotherapy reduced the risk of progression of patients with mCRC. 7,8 Therefore, it is of clinical significance to investigate potential strategy to improve the CRC response to cetuximab. Moreover, not all mCRC patients with RAS-wild type (WT) respond to cetuximab treatment, and even some patients with initial response may acquire resistance later after the treatment.…”
mentioning
confidence: 99%